2018
DOI: 10.1093/mnras/sty329
|View full text |Cite
|
Sign up to set email alerts
|

Optical photometric variable stars towards the Galactic H ii region NGC 2282

Abstract: We report here CCD I-band time-series photometry of a young (2−5 Myr) cluster NGC 2282 to identify and understand the variability of premain-sequence (PMS) stars. The I-band photometry, down to ∼ 20.5 mag, enables us to probe the variability towards the lower mass end (∼ 0.1 M ⊙ ) of the PMS stars. From the light curves of 1627 stars, we identified 62 new photometric variable candidates. Their association with the region was established from Hα emission and infrared (IR) excess. Among 62 variables, 30 young va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…Figure 11 displays spectral index against rotation period. While the number of stars is too small to provide a good statistical significance, the general form of the distribution is quite similar to what is seen in the ONC (Herbst et al 2002), IC 348 (Nordhagen et al 2006) or NGC 2282 (e.g., Dutta et al 2018a). One CTTS star (ID6506) has the period less than 2 days and another CTTS (ID1564) is relatively slow rotators.…”
Section: Correlation Between Photometric Variability and Circumstellasupporting
confidence: 53%
See 3 more Smart Citations
“…Figure 11 displays spectral index against rotation period. While the number of stars is too small to provide a good statistical significance, the general form of the distribution is quite similar to what is seen in the ONC (Herbst et al 2002), IC 348 (Nordhagen et al 2006) or NGC 2282 (e.g., Dutta et al 2018a). One CTTS star (ID6506) has the period less than 2 days and another CTTS (ID1564) is relatively slow rotators.…”
Section: Correlation Between Photometric Variability and Circumstellasupporting
confidence: 53%
“…The identification of variable stars was performed by means of careful inspection of the light curves. First, we estimated RMS (σmag) deviation of relative magnitudes for all the stars (e.g., Dutta et al 2018a). In the Figure 4, the lower envelope represents an expected trend of σmag as a function of stellar brightness, where σmag increases with Iinst magnitudes since SNR decreases accordingly.…”
Section: Selection Of Variable Candidatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lata et al (2012Lata et al ( , 2016 have found a decrease of rotation period of PMS variables with the increase in their masses, but no conclusive result was found for age-period correlation. Dutta et al (2018) have found a correlation between variability amplitude with IR excess in PMS stars, indicating that in the disc bearing stars, the accretion phenomena plays a significant role in their energy output. Unfortunately, we are still not able to construct a complete paradigm for disc evolution and a commonly adopted scenario for early stellar evolution that satisfies all the available observational constraints.…”
Section: Introductionmentioning
confidence: 97%